2022
DOI: 10.3389/fevo.2022.1018581
|View full text |Cite
|
Sign up to set email alerts
|

Built environment and travel behavior in rural areas: A scientometric literature review

Abstract: With the rise of global urbanization, the rural built environment has undergone tremendous changes. As such, the rural built environment impacts on residents’ daily travel behavior is getting more researchers’ attention. To date, most of the research focuses on urban areas in developed countries. To understand the state-of-the-art of interplay between the rural built environment and travel behaviors and to identify future research directions, this study adopts a science mapping approach to identify the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…It has been used in other studies, such as Oliveira et al [13] and Corrêa et al [14], and based on them, this paper adopts similar procedures, implementing minor changes to guarantee the replicability of the methods. Among mobility-related research, we can also find similar and recent uses of the proposed procedure in Ao et al [15] and Alidadi and Sharifi [16], however, without the in-depth analysis of papers. The use of these tools for bibliometric analysis may become more and more popular in systematic literature review papers since the amount of data can exceed the human capacity to analyze it in a limited period of time.…”
Section: Analysis Methodsmentioning
confidence: 59%
“…It has been used in other studies, such as Oliveira et al [13] and Corrêa et al [14], and based on them, this paper adopts similar procedures, implementing minor changes to guarantee the replicability of the methods. Among mobility-related research, we can also find similar and recent uses of the proposed procedure in Ao et al [15] and Alidadi and Sharifi [16], however, without the in-depth analysis of papers. The use of these tools for bibliometric analysis may become more and more popular in systematic literature review papers since the amount of data can exceed the human capacity to analyze it in a limited period of time.…”
Section: Analysis Methodsmentioning
confidence: 59%
“…Several studies have shown that walking accessibility directly affects residents' subjective well-being (17,19,31). However, existing studies are mainly based on linear models, ignoring the complex and diverse non-linear influence relationships that may exist (29,32,33). Therefore, this study aimed to explore the non-linear effects of walking accessibility on subjective well-being in rural older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the relationship between rural road environment and travel mode has received attention. Li et al ( 17 ), Nathan et al ( 22 ) and Ao et al ( 23 ) found that the road environment is an important influence on rural residents’ choice of travel mode. Zacharias and Liu ( 24 ) indicated that travelers’ perception of the environment and satisfaction varies by travel mode.…”
Section: Introductionmentioning
confidence: 99%